2013
DOI: 10.1007/s10863-013-9508-x
|View full text |Cite
|
Sign up to set email alerts
|

Bax induces cytochrome c release by multiple mechanisms in mitochondria from MCF7 cells

Abstract: Bax, a pro-apoptotic member of the Bcl-2 family of proteins has the ability to form transmembrane pores large enough to allow cytochrome c (Cyt c) release, as well as to activate the mitochondrial permeability transition pore (mPTP); however, no differential study has been conducted to clarify which one of these mechanisms predominates over the other in the same system. In the present study, we treated isolated mitochondria from MCF7 cells with recombinant protein Bax and tested the efficacy of the mPTP inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…These proteins are regulators of mitochondrial membrane permeability and intermembrane space protein efflux, according to the opposing fractions of the anti-apoptosis members and pro-apoptosis members (32,33). Bax accelerates programmed cell death and undergoes a conformational change that causes translocation to the mitochondrial membrane, leading to the release of cytochrome c, which then triggers apoptosis (34). Cordycepin enhanced the expression level of Bax and decreased the expression level of Bid in the present study.…”
supporting
confidence: 54%
“…These proteins are regulators of mitochondrial membrane permeability and intermembrane space protein efflux, according to the opposing fractions of the anti-apoptosis members and pro-apoptosis members (32,33). Bax accelerates programmed cell death and undergoes a conformational change that causes translocation to the mitochondrial membrane, leading to the release of cytochrome c, which then triggers apoptosis (34). Cordycepin enhanced the expression level of Bax and decreased the expression level of Bid in the present study.…”
supporting
confidence: 54%
“…Bax, a bcl2 family protein, interacts with bcl2 protein and induces apoptosis. Bax is reported to increase the opening of the mitochondrial voltagedependent anion channel, which leads to the loss in membrane potential and the release of cytochrome c. The increase in bax and cytochrome c is in accordance with the previous findings (Gómez et al, 2013). …”
Section: Discussionsupporting
confidence: 92%
“…Taken together, these findings directly revealed that DSePA blocked high glucose-induced mitochondrial dysfunction. Bcl-2 family is thought to be important in regulation of Δψm and mitochondria-mediated apoptosis [21]. The balance between pro-apoptotic proteins (Bax, Bad, and Bid) and antiapoptotic proteins (Bcl-2 and Bcl-xL) decides the cells fate [22].…”
Section: Dsepa Blocks High Glucose-induced Mitochondrial Dysfunction mentioning
confidence: 99%